The Influence of Reading Comprehension and Fluency on Science and Maths Reasoning in Pre-service Primary Education Teachers - Sánchez Huete, Juan Carlos; Pérez Bonet, Gregorio; Méndez Coca, David; Rodríguez López, Antonio; Martín Nieto, Marta (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2019)
According to the results from the last PISA report, scientific and mathematic education in Spain does not show outstanding results regarding the solution of scientific or mathematic problems. Why is this happening then? The research presented in this paper aims to establish a connection between the reading comprehension and fluency of pre-service Primary Education teachers and their ability for reasoning in the fields of science and maths. The main purpose is to measure the reading comprehension, the reading fluency and the reasoning capacity in a sample of 198 university students from Madrid who are doing their initial teacher training in Primary Education.